Wellbeing in education unveiled: teachers' insights in Irish post-primary education - Niamh O'Brien; Wesley O'Brien; John Goodwin (Springer, 2024)
Abstract This study investigates and explores post-primary teachers' perceptions and attitudes towards wellbeing in Irish schools, identifying the enabling activities, factors, and barriers to promoting wellbeing using the National Council for Curriculum and Assessment (NCCA) Junior Cycle Wellbeing Guidelines. Using mixed-method design, self-report questionnaires (N = 60) and semi-structured interviews (N = 10) were used with a sample of post-primary teachers from various career stages (6.7% having 1-2 years of experience, 26.7% with 3-5 years of experience, 15% with 5-8 years of experience, and the majority, 51.7%, having more than 8 years of experience). Subject teaching curricular areas included a broad spectrum, namely Physical Education (PE) (71.7%), Irish (33.3%), Mathematics (16.7%), English (10%) and Social, Personal and Health Education (SPHE) (10%). Participating schools included a mix of rural and urban settings, with 91.7% of the sample located in the South West region of Ireland. Schools represent a diverse range of educational environments, ranging from public religious (33.3%) to vocational community (23.3%), to public multi-denominational (20%), to private (1.7%) and to other school type settings (11.6%). A snowball sampling technique was used for survey data collection, while convenience sampling was used for the interviews. A custom self-report questionnaire was developed for this study, with reliability and validity established through piloting and expert review. SPSS software was used for quantitative analysis. A significant positive association was found between teachers' familiarity with the guidelines and their perceptions of Wellbeing Guideline effectiveness in supporting student wellbeing (χ2 (6, N = 60) = 54.7, p < 0.001). Additionally, a shared vision of wellbeing among school communities emerged as crucial for adopting a whole-school approach (χ2 (4, N = 60) = 12.9, p = 0.012). This strengthens the evidence that the alignment of perspectives on wellbeing is not just beneficial but crucial for the systemic and sustained implementation of wellbeing initiatives in schools. It indicates that greater awareness and understanding of wellbeing and the Wellbeing Guidelines through Professional Development enhances teachers' buy-in and confidence in the successful promotion of wellbeing. A qualitative analysis of interviews (N = 10) identified barriers like time constraints, limited teacher skillsets, and the current prioritisation of academic achievement over social-emotional learning. Teachers emphasised that staff wellbeing is essential for student wellbeing and that there is a need for more professional development and practical wellbeing approaches to be provided to schools. Finally, the study portrays the complex interplay of individual, interpersonal, community, and societal influences on wellbeing, mapped across the Bronfenbrenner Ecological Framework, emphasising the multidimensional nature of wellbeing in educational settings. It provides stakeholders with an illustration of how wellbeing can be practically and contextually integrated across a school or organisation. Potential limitations of the study include a narrow generalisability of the findings due to the majority of participants being PE teachers. In Ireland, it is important to note that PE teachers are a cohort who have curriculum responsibility on the delivery of Wellbeing as an area of learning for students aged 12 to 16 years old.